The combined status of ATM and p53 link tumor development with therapeutic response - Jiang, Hai; Reinhardt, H. Christian; Bartkova, Jirina; Tommiska, Johanna; Blomqvist, Carl; Nevanlinna, Heli; Bartek, Jiri; Yaffe, Michael B.; Hemann, Michael T. (Genes & development, 2009)
While the contribution of specific tumor suppressor networks to cancer development has been the subject of considerable recent study, it remains unclear how alterations in these networks are integrated to influence the response of tumors to anti-cancer treatments. Here, we show that mechanisms commonly used by tumors to bypass early neoplastic checkpoints ultimately determine chemotherapeutic response and generate tumor-specific vulnerabilities that can be exploited with targeted therapies. Specifically, evaluation of the combined status of ATM and p53 , two commonly mutated tumor suppressor genes, can help to predict the clinical response to genotoxic chemotherapies. We show that in p53 -deficient settings, suppression of ATM dramatically sensitizes tumors to DNA-damaging chemotherapy, whereas, conversely, in the presence of functional p53, suppression of ATM or its downstream target Chk2 actually protects tumors from being killed by genotoxic agents. Furthermore, ATM -deficient cancer cells display strong nononcogene addiction to DNA-PKcs for survival after DNA damage, such that suppression of DNA-PKcs in vivo resensitizes inherently chemoresistant ATM -deficient tumors to genotoxic chemotherapy. Thus, the specific set of alterations induced during tumor development plays a dominant role in determining both the tumor response to conventional chemotherapy and specific susceptibilities to targeted therapies in a given malignancy.